A new latch-free LIGBT on SOI with very high current density and low drive voltage. (January 2016) - Olsson, J.; Vestling, L.; Eklund, K.-H.
Abstract: A new latch-free LIGBT on SOI is presented. The new device combines advantages from both LDMOS as well as LIGBT technologies; high breakdown voltage, high drive current density, low control voltages, at the same time eliminating latch-up problems. The new LIGBT has the unique property of independent scaling of the input control device, i.e. LDMOS, and the output part of the device, i.e. the p–n–p part. This allows for additional freedom in designing and optimizing the device properties. Breakdown voltage of over 200 V, on-state current density over 3 A/mm, specific on-resistance below 190 mΩ mm 2, and latch-free operation is demonstrated.